Antimicrobial resistance in Indonesia: A comprehensive One Health analysis and strategic roadmap for mitigation - Ni Luh Putu Indi Dharmayanti; Muhammad Khaliim Jati Kusala; Harimurti Nuradji; Diana Nurjanah (International Journal of One Health)
Background and Aim: Antimicrobial resistance (AMR) has emerged as one of the most critical global health challenges and poses significant threats to human, animal, and environmental health. Indonesia, like many other developing nations, is facing widespread AMR because of the overuse and misuse of antibiotics in humans, livestock, aquaculture, and agriculture. The interconnected nature of AMR requires a holistic approach to understand its prevalence, pathways, and impact. A One Health perspective, which integrates human, animal, and environmental health, is vital for comprehensively and effectively addressing AMR. This study is significant because it provides a detailed analysis of AMR in Indonesia and identifies critical resistance patterns across various bacterial species and antibiotics. This study highlights reservoirs of resistance, such as wastewater and food-producing animals, which serve as major pathways for the spread of resistant genes. Furthermore, this study examines the policy landscape in Indonesia, emphasizing the need for data-driven interventions and multi-sectoral collaboration. This study offers insights into AMR’s economic, health, and social implications and aligns with global and national AMR mitigation frameworks. The primary aim of this study was to evaluate the current state of AMR in Indonesia, focusing on the environmental, animal, and human health sectors. The One Health approach identifies key resistance patterns, transmission pathways, and contributing factors. In addition, the study proposes a research roadmap to guide future initiatives, emphasizing the development of rapid diagnostics, therapeutic innovations, and improved surveillance systems to combat the growing threat of AMR in Indonesia.